2012
DOI: 10.1111/1567-1364.12023
|View full text |Cite
|
Sign up to set email alerts
|

Repression vs. activation ofMOX,FMD,MPP1andMAL1promoters by sugars inHansenula polymorpha: the outcome depends on cell's ability to phosphorylate sugar

Abstract: A high-throughput approach was used to assess the effect of mono- and disaccharides on MOX, FMD, MPP1 and MAL1 promoters in Hansenula polymorpha. Site-specifically designed strains deficient for (1) hexokinase, (2) hexokinase and glucokinase, (3) maltose permease or (4) maltase were used as hosts for reporter plasmids in which β-glucuronidase (Gus) expression was controlled by these promoters. The reporter strains were grown on agar plates containing varied carbon sources and Gus activity was measured in perme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…We cloned the maltase gene MAL1 of Op about 15 years ago (Liiv et al , ) and later studied its regulation (Alamäe et al , ; Suppi et al , ). A study of crude cell extracts of MAL1 ‐expressing E. coli (Liiv et al , ) showed that the Op maltase hydrolysed not only maltose and sucrose but also α ‐MG (for structure, see supporting information, Figure S1), which is a synthetic analogue of isomaltose and a substrate for isomaltases (Yamamoto et al ., ; Teste et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…We cloned the maltase gene MAL1 of Op about 15 years ago (Liiv et al , ) and later studied its regulation (Alamäe et al , ; Suppi et al , ). A study of crude cell extracts of MAL1 ‐expressing E. coli (Liiv et al , ) showed that the Op maltase hydrolysed not only maltose and sucrose but also α ‐MG (for structure, see supporting information, Figure S1), which is a synthetic analogue of isomaltose and a substrate for isomaltases (Yamamoto et al ., ; Teste et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the phenotype of a HXT deletion strain [14], and also with the observation that the AMP/ATP ratio reflects the glucose level inside the cell (a high AMP/ATP ratio leads to activation of Snf1 [9], a kinase directly involved in gene regulation by carbon sources). However, most likely the processed metabolite of monosaccharides in the cell–glucose-6-phosphate–is the main signal that activates glucose repression [15]. …”
Section: Introductionmentioning
confidence: 99%
“…Our data on Op indicated that monosaccharides (glucose and fructose) produced at intracellular hydrolysis of disaccharides repress the MAL1 promoter and their phosphorylation is obligatory for the repression. At the same time, temporary accumulation of unphosphorylated hydrolysis products was shown to activate the promoter [ 11 ]. The growth of Op on disaccharides is assumingly complicated [ 11 ], because hydrolysis products of disaccharides that promote initial derepression of MAL genes will later cause repression when their phosphorylated species accumulate.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, temporary accumulation of unphosphorylated hydrolysis products was shown to activate the promoter [ 11 ]. The growth of Op on disaccharides is assumingly complicated [ 11 ], because hydrolysis products of disaccharides that promote initial derepression of MAL genes will later cause repression when their phosphorylated species accumulate. Therefore, expression of AGT and AG proteins has to be finely adjusted with further glycolytic flux to provide an appropriate expression level of MAL genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation